A Systematic Review of Function-Based Replacement Behavior Interventions for Students With and At Risk for Emotional and Behavioral Disorders. (September 2016) - McKenna, John William; Flower, Andrea; Adamson, Reesha
Students with emotional and behavioral disorders and students considered at risk often have social deficits. Although social skills interventions are often provided to this student population, there are some concerns regarding how these interventions are conceived and provided. One possible way to improve the effectiveness of social skills interventions is to use functional behavior assessment data to tailor the interventions to a student's individual needs and the contexts in which social skills deficits and problem behaviors occur. This approach is commonly referred to as replacement behavior training. In this study, the literature on function-based replacement behavior interventions is systematically reviewed. In addition, studies are evaluated according to the What Works Clearinghouse design and evidence standards for single-case research. Although this research base does not meet the What Works Clearinghouse replication standards, function-based replacement behavior interventions appear to be a promising practice for addressing problem behaviors. Implications for practice, areas for future research, and study limitations are discussed.